(untitled) (Damascus University Journal of agriculture sciences, 2021)
The main objective of this research was to study the knowledge-level of farmers about Integrated Pest Management (IPM) of olive, and study some personal factories that might affect the knowledge Level of IPM in Lattakia. Data were collected in 2016 by a questionnaire and personal interview with (150) farmers representing the sample of this research in three villages (Al Shamiya, Borj Al Kassab, alkallof) in lattakia Governorate in Syrian coast. The results showed a low knowledge-level of farmers about IPM, and there were significant positive relationships between respondents knowledge degrees of (IPM) of olive and the independent variables i.e. level of education and resource of information, and a significant negative relationship with agricultural experience. The researchers recommended to do more work dissemination the concept of IPM to reduce using of pesticides and fertilizers as can as possible through intensified programs and extension activities.